Phenotypic and genotypic profiling of swine-derived Shiga toxin-producing Escherichia coli over a decade in South Korea: a framework for edema disease vaccine candidate strains selection - Park, Gyeong-Seo; Kim, Hwan-Ju; Cho, Myung A.; Kim, Seung-Chai; Jeong, Chang-Gi; Ryu, Ji-Hyun; Kwon, Woo Ju; Lee, Hyo Jeong; Kang, Jae-Gu; Jung, Byeong Yeal; Kim, Myung Hyee; Kim, Chonghan; et al. (Frontiers in Microbiology, 2025)
IntroductionShiga toxin-producing Escherichia coli (STEC), particularly strains harboring Stx2e, are the primary cause of edema disease (ED) in swine, leading to acute mortality and economic loss. Despite the use of antimicrobials and autogenous vaccines, control remains inadequate due to high genetic variability and upregulated multidrug resistance (MDR). In Korea, field outbreaks persist in post-weaning pigs, underscoring the need for immunologically relevant vaccine candidates. This study aimed to characterize STEC isolates from 2014 to 2025 and identify representative strains for vaccine development through integrated molecular, phenotypic, and resistance profiling.MethodsA total of 184 STEC isolates were collected from clinical swine cases submitted between 2014 and 2025. Isolates were characterized via PCR-based virulence gene profiling, cytotoxicity assays using Vero cells, antimicrobial susceptibility testing, and Gompertz-modeled in vitro growth kinetics. Principal component analysis (PCA) and multivariate clustering were applied to assess phenotypic patterns. Two candidate vaccine strains were selected using an integrated scoring system incorporating virulence, cytotoxicity, metabolic fitness, and antimicrobial resistance profiles.ResultsA total of 184 STEC isolates were recovered from swine diagnostic submissions across nine Korean provinces between 2014 and 2025. Genotypic analysis identified 29 virulence gene profiles, with Stx2e and F18 being predominant. Phenotypic assays revealed that Stx2e-only isolates exhibited superior growth kinetics and higher cytotoxicity than other genotypes. Antimicrobial susceptibility testing demonstrated widespread multidrug resistance, especially to sulfonamides, β-lactams, and aminoglycosides. Principal component analysis showed clustering based on toxin profiles and metabolic traits. No non-MDR isolates were observed, underscoring the high resistance burden. Two Stx2e-positive isolates with complementary F18 profiles, strong proliferation (>4.0 × 108 CFU/mL), and consistent cytotoxicity were selected as optimal vaccine candidates. Whole-genome sequencing confirmed their genetic stability and field relevance, supporting their advancement into vaccine development pipelines.ConclusionThis study provides a decade-long surveillance-based framework for rational STEC vaccine design in swine. Two Stx2e-positive strains were selected as representative immunogen candidates based on integrated genotypic and phenotypic criteria. These findings support the development of scalable, field-relevant vaccine platforms aimed at reducing antimicrobial use and controlling edema disease in Korean pig populations.